In vitro efficacy of Daptomycin against clinical isolates of Methicillin-resistant Staphylococcus aureus (MRSA) - Asim Ali Shah; Shahid Ahmad Abbasi; Yasir Ali; Ayesha Maqbool (Journal of the Pakistan Medical Association, 2020)
This descriptive cross-sectional study was performed in the Department of Microbiology, Fauji Foundation Hospital, Rawalpindi, from March 2019 to September 2019 to determine the in vitro efficacy of Daptomycin against clinical isolates of Methicillin-Resistant Staphylococcus aureus (MRSA). Consecutive non-probability sampling technique was used and a total number of 270 patients’ Pan Cultures having MRSA growth on Cefoxatin Disc with size less than 22 mm zone size were included in the study. Cultures were inoculated on MacConkey, Chocolate and Blood agar and then incubated for 24 hours at 37 degree Celsius. After incubation, Coagulase test, Catalase test and Gram staining technique were used for further identification. Minimum Inhibitory Concentration (MIC) of the isolates for Daptomycin was obtained by using E strips (Oxoid UK) according to Clinical & Laboratory Standards Institute (CLSI) guidelines. Continuous...